2022
DOI: 10.1111/pcmr.13033
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of an immortalized human giant congenital melanocytic nevi cell line

Abstract: Congenital melanocytic nevi are benign melanocytic tumors that are present at birth. When the diameter of the nevus reaches 20 cm in projected adult size, it is known as a giant congenital melanocytic nevus (GCMN) (Alikhan et al., 2012;Tannous et al., 2005). The estimated incidence of GCMN is between 1/50,000 and 1/20,000 births. GCMN could involve any area of the body surface, and the pigmented appearance presents a heavy psychological burden to the patients and their families. Simultaneously, GCMN has a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…85 As therapy targeting MAPK and PI3K pathways has shown promising antitumour activity in NRAS-mutated melanomas, thus, theoretically, it may be effective for CMN harboring NRAS mutations as well. [86][87][88] Here, we summarize some in vitro studies on targeted therapy of nevus cells (Table 3). Basu et al reported that NRAS mutant nevus cells were resistant to vemurafenib (a BRAF inhibitor), and MEK162…”
Section: Targeted Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…85 As therapy targeting MAPK and PI3K pathways has shown promising antitumour activity in NRAS-mutated melanomas, thus, theoretically, it may be effective for CMN harboring NRAS mutations as well. [86][87][88] Here, we summarize some in vitro studies on targeted therapy of nevus cells (Table 3). Basu et al reported that NRAS mutant nevus cells were resistant to vemurafenib (a BRAF inhibitor), and MEK162…”
Section: Targeted Therapymentioning
confidence: 99%
“…91 However, the study by Yu et al further indicated that navitoclax (a Bcl-2 family inhibitor) exhibited an even better inhibitory effect on nevus cells than PI3K/Akt inhibitors by promoting apoptosis. 87 Therefore, the therapies that combine inhibitors targeting different mediators may be worth exploring in the future.…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation